Probability of a two hop connection in a random mobile network - 283038 S. M. Elizabethrani Allappan (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2005